Role of Various Estrus Induction and Synchronization Protocols in Influencing Plasma Progesterone, Metabolic Profile and Fertility in Acyclic Buffaloes - Prajapati, JP; Patel, DM; Dhamui, AJ; Patel, JA; Hadiya, KK; Chaudhri, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out under field conditions on 50 acyclic/ anestrus buffaloes to evaluate the efficacy of four standard estrus synchronization protocols, viz., Doublesynch, Estradoublesynch, Ovsynch, and Ovsynch Plus (10 buffaloes in each protocol, and in untreated control group) in terms of estrus induction response, conception rates at induced estrus with FTAI and monitoring plasma progesterone, protein and cholesterol profile at different time intervals during treatment and day 12 post-AI. All the animals received pre-synchronization treatment, i.e., Inj. 100 mg ivermectin s/c, Inj. tono-vita 20 ml, and multi-minerals 1 bolus daily for 7 days. The conception rates obtained at induced estrus (FTAI) were 50.0, 40.0, 30.0 and 50.0 % with Doublesynch, Estradoublesynch, Ovsynch and Ovsynch Plus protocol, respectively. The rests were taken as non-conceived ones. The plasma progesterone concentrations monitored on day 0 (start of treatment), 7/9 (PGF2α injection), 10/12 (FTAI) and on day 12 post-AI revealed significant (p<0.01) effect of sampling days in all four protocols with higher values on day of PGF2α injection and on day 12 post-AI compared to other days. Moreover, the plasma progesterone concentrations were significantly (p<0.05) higher in conceiving than the non-conceiving buffaloes on day 12 post-AI in all 4 protocols. The mean plasma protein and cholesterol profile did not differ significantly between days in any of the protocols. The animals under Doublesynch protocol however had significantly higher protein values as compared to Ovsynch and Ovsynch Plus protocols. Moreover, the non-conceiving buffaloes under Ovsynch Plus protocol had significantly (p<0.05) lower mean plasma protein (5.73±0.15 vs. 6.49±0.13 g/dl) and cholesterol (57.42±1.19 vs. 76.68±1.85 mg/dl) concentrations compared to their counterparts. It was concluded that all four hormonal protocols improved plasma progesterone profile and conception rates in acyclic buffaloes without altering plasma protein and cholesterol profile. The maximal benefit was with Doublesynch and Ovsynch plus protocols, hence these can be practiced under field conditions to manage acyclic buffaloes.